Pendidikan Melalui Metode Kombinasi Ceramah dan Diskusi Tentang HIV/AIDS Pada Kader Posyandu Di Kecamatan Gringsing Kabupaten batang Jawa Tengah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The spread out of HIV/AIDS in all levels of community or elements has become greater. This virus is an important health problem that necessary to be solved soon. Communities, in general, and integrated service cadre, specifically, were not yet known, react and respond to activities in the effort of HIV/AIDS virus prevention, so that a clearer information process is needed